Analysis Of Interests of Young Generation in Becoming an Islamic Bank Leader - Dyah Anindita Nur Wulandari; Hermawan Adinugraha; Muhammad Shultoni (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2024)
This research is based on the observation of researchers related to the number of Muslim communities more inclined to be interested in using the services of conventional banks than Islamic banks. This research uses a qualitative method with a descriptive approach. This study aims to analyze the determinants of the lack of interest from the younger generation to become customers of Islamic banks. The data analysis techniques used are interviews, observations, and documentation. Based on the results of the interview, it is suggested that the determinants of the lack of interest from the younger generation to become customers of Islamic banks are influenced by several things. First, promotional factors from Islamic banks to the public. Islamic banks are considered less competent in introducing their products. Second, infrastructure factors and unsatisfactory office networks. Infrastructure factors and office networks are an obstacle to other people's interest in switching to Islamic banks. Third, competitive factors that gain more trust make competition difficult.  The tight competition between Islamic banks and conventional banks exacerbates the existing situation.